Challenges Affecting Technical Vocational Education and Training in Trinidad and Tobago: Stakeholders’ Perspective - Mack, Abede Jawara; White, Daniel (Journal of Technical Education and Training, 2019)
The paper focused on the challenges impacting Technical Vocational Education and Training (TVET) within Trinidad and Tobago (T&T). The study highlighted issues plaguing TVET, with insights emanated from stakeholders within TVET institutions. The challenges that presented itself showed TVET in T&T faces copious amount of problems. Stigma, Attrition, and Quality teaching were some of the key problems affecting TVET in T&T. The researcher utilised a qualitative approach to gather data from stakeholders within the institutions. The data was put forward by way of a thematic analysis approach. Focus groups and interviews were used to extract many details that gave the study deep and rich insights on TVET and the challenges emanating at present. Two main themes emerged from the data: challenges and resources. These two areas were further broken down into sub themes. The study also showed that TVET institutions are incapable of treating with some of the issues they faced, and it requires intervention from the central government to address the macro problems that plagued TVET. The research focused on four TVET institutions that are tertiary level institutions of learning. Additionally, the study showed very persuasively that TVET is experiencing a number of significant challenges in T&T. The issues that face the institutions are very complex and which they may not be able to address in a significant way. These challenges require intervention from the governmental level, these matters require the right and adequate leadership as a very important factor in moving TVET forward.